HOME ANEW Reclaiming an emotionally sensitive space - Arnholm, Edvin (My University, 2023)
This thesis aims to explore the process of building a house in a personal and emotionally sensitive space while respecting the heritage of the family and the site. The primary objective is to provide spaces to gather family and friends, while respecting the memory of what once was. This is done by creating a comfortable and functional space where the family can create new memories together. The outcome is a design proposal for a vacation home, next to the existing building. The starting point for the thesis is to trace the family heritage on the site, in the village of Mölltorp in Västra Götaland. To provide contextualization about the site and the house, the early stages of the process were spent sketching different aspects of the existing building, in research by design methodology. A phase focusing on research for design followed, conducted through literature studies. This was followed by the design phase, where the research question is explored through architectural design. The design process intended to provide an answer to the research question, where the memories of how the site has been used in the past has been elemental in shaping the new design proposal. In conclusion this thesis aims to provide a framework for designing a new building in a personal and emotionally sensitive space without feeling intrusive to the memories, or worse, like a poorly executed replica that could potentially harm the delicate emotional bonds that exist on the site.
Keywords: Emotionally sensitive spaces, vernacularity, nostalgia, residential